Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail